(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2020)
The critical reading skill of textbooks in history learning is significant to be developed. This research is motivated by the low critical reading skill of students in learning history. An indication is seen from the ability to find and compare reading sources, analyze textbooks, take notes from reading, and share information from the reading analysis. Based on these, the researcher formulated several problems: first, how to plan learning using the Search, Solve, Create, and Share (SSCS) method. Second, how to implement the Search, Solve, Create, and Share (SSCS) method. Third, how to improve learning using the Search, Solve, Create, and Share (SSCS) method. Fourth, how to overcome the problems resulted from the application of the Search, Solve, Create, and Share (SSCS) method. This study aimed to improve students’ critical reading skills of history textbooks in history learning. This study used a classroom action research design of the Kemmis and Taggart model which consists of planning, implementing, observing, and reflecting. Aspects studied from textbook’s critical reading skill are selecting information from history textbooks that are suitable for discussion, finding information from history textbooks, analyzing reading content in history textbooks, conducting questions and answers to teachers or friends about learning material in books, historical texts, making notes based on reading results from history textbooks, as well as sharing works based on reading. The results showed that it is possible to improve the textbook’s critical reading skill in history learning. This is indicated by the improvement of critical reading skills in the learning process in each cycle.